ANALISIS SEMANGAT KERJA PADA PEGAWAI SEKREARIAT DAERAH KABUPATEN MAMUJU TENGAH BAGIAN UMUM - Ludi Indrawan; Agung Widhi Kurniawan; Ilham Wardhana Haeruddin (Cross-border, 2022)
Work spirit is an attitude that needs to be possessed by employees, success in the work process to achieve predetermined goals is greatly influenced by the morale of the employee himself. Morale is something that affects the implementation of the work of each employee, so called because morale is closely related to the level of satisfaction and pleasure with each implementation of their work. However, with the pandemic pandemic, several factors have emerged that can affect employee morale and have an impact on their productivity. This study aims to identify factors that affect the enthusiasm of employees in carrying out their work, as well as find a solution to the problem of morale experienced by employees. The search for the work spirit factors of the employees begins with the work environment, workload, and compensation, then identifies the various sources of work spirit of the employees. The results of this study use a qualitative method where data collection is carried out by interviews and observations so as to be able to dig deeper into information about employees. As the object of this study are employees of the regional secretariat office of Central Mamuju Regency, especially in the general section. The results obtained from this study state that the work spirit of the employees is influenced by several aspects such as the work environment, workload, and compensation of employees.